2018
DOI: 10.3897/nl.41.23090
|View full text |Cite
|
Sign up to set email alerts
|

Agrotis fatidica (Hübner, 1824) species-group revisited, with description of two new species from the Alps and the Pyrenees (Lepidoptera, Noctuidae)

Abstract: An integrative taxonomic analysis of the European species of theAgrotisfatidicaspecies-group is presented with special reference to the European sister taxa ofA.fatidica(Hübner, 1824); in addition, a general overview of the entire species-group is given. The remarkable differences found in the barcodes of the Central and Western European populations ofA.fatidica(sensu lato) led us to recognise isolated species of theA.fatidicacomplex. Two new species,A.mayrorumsp. n.(Northern Italy and the French Alps) andA.ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In the recent past an increasing number of cryptic species has been detected in various groups of arthropods on the basis of molecular differences. However, in these cases, morphological differences could be found that, although slight and often inconspicuous, were constant, and thus would justify the description of a new taxon (species) or re-installment of a species previously regarded as a synonym (Ronkay and Huemer 2018). Regarding Ornatoraphidia flavilabris the conditions are quite different.…”
Section: Discussionmentioning
confidence: 95%
“…In the recent past an increasing number of cryptic species has been detected in various groups of arthropods on the basis of molecular differences. However, in these cases, morphological differences could be found that, although slight and often inconspicuous, were constant, and thus would justify the description of a new taxon (species) or re-installment of a species previously regarded as a synonym (Ronkay and Huemer 2018). Regarding Ornatoraphidia flavilabris the conditions are quite different.…”
Section: Discussionmentioning
confidence: 95%
“…In a few genera restricted to the alpine and subnival altitudinal zones of the Alps and other European high mountains, brachyptery is a consistent phenomenon, including in particular the genera Sattleria (Gelechiidae) (Pitkin and Sattler 1991;Huemer and Hebert 2011;Huemer and Timossi 2014;Timossi and Ruzzier 2020;Timossi and Huemer 2022) and Sphaleroptera (Tortricidae) (Whitebread 2006;Timossi and Ruzzier 2023). In other genera such as Kessleria (Yponomeutidae) (Huemer and Mutanen 2015;Huemer and Tarmann 1992), Oxypteryx (Gelechiidae) (Huemer et al 2013), Elophos (Geometridae) (Müller et al 2019) and Agrotis (Noctuidae) (Ronkay and Huemer 2018) there are different stages of brachyptery, from nearly fully winged to strongly pronounced wing reduction in high altitude taxa. Furthermore, brachyptery can also be restricted to few species within a genus, for example Elachista brachypterella (Elachistidae) (Klimesch 1990).…”
Section: Discussionmentioning
confidence: 98%
“…Cryptic diversity has been found in many different families of European Lepidoptera during the last years, progress mainly driven by the implementation of molecular methods and newly collected samples resulting from better access to remote parts of the continent. The majority of cryptic species seems to be hidden among various groups of so-called traditional “micromoths” ( Huemer et al 2020 ; Lopez-Vaamonde et al 2021 ), whereas only a few overlooked species have been detected in the more “spectacular” taxonomic groups such as Papilionoidea ( Dincă et al 2021 ) or recently in the “macromoths” ( Ronkay and Huemer 2018 ; Šumpich and Jagelka 2021 ). The majority of newly detected cryptic species seems to occur in allopatry, particularly in mountain areas of southern Europe, and they often cause ongoing taxonomic problems ( Mutanen et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%